Use of Oxygen in the Emergency Department - Riccardo Guglielmi; Antonio Campanella; Jesús Villar; Carlos Ferrando (Seminars in Respiratory and Critical Care Medicine, 2026)
ABSTRACT Oxygen is one of the most frequently used treatments in the emergency department (ED), but it should be prescribed and reassessed as an active therapy rather than left as a harmless default. Acute hypoxemia may reflect ventilation-perfusion mismatch, shunt, hypoventilation, impaired oxygen transport, circulatory failure, or a combination of these mechanisms. For this reason, the response to oxygen, the choice of device, and the need for escalation depend less on the SpO2 value alone than on the physiology behind it. Current evidence has moved practice away from liberal oxygen administration and toward titration to predefined targets, aiming to correct clinically important hypoxemia while avoiding unnecessary hyperoxemia. Most acutely ill adults should receive oxygen when they are hypoxemic or clinically unstable, whereas patients at risk of hypercapnic respiratory failure, especially those with COPD exacerbation, require controlled oxygen therapy and early blood gas assessment. Conventional devices remain appropriate for many patients, but their performance varies with inspiratory demand, flow, mask fit, and entrainment of room air. High-flow nasal oxygen can improve comfort, humidification, oxygen delivery, dead-space washout, and work of breathing in selected patients with acute hypoxemic respiratory failure, but preserved saturation must not delay escalation when respiratory distress, shock, altered mental status, or worsening gas exchange suggests treatment failure. Good oxygen practice in the ED means knowing when to start oxygen, how to titrate it, when to stop it, and when oxygen is not sufficient.